Dampak Membuang Sampah di Pesisir Pantai Binongko, Kelurahan Kalabahi Kota, Kecamatan Teluk Mutiara - Merlinda Thabita Mapada; Melki Imamastri Puling Tang; Nehemia Fanpada; Ita Trisnawati Malaipada; Karolina Milenia Parera (Yayasan Literasi Sains Indonesia, 2023)
Binongko Beach is one of the areas located in the Kalabahi Kota Village, Teluk Mutiara District, Alor Regency, East Nusa Tenggara. This beach is one of the beaches that looks very dirty because it is filled with a lot of garbage, there is a lot of trash scattered on the coast. This research will be carried out using qualitative methods as research observations, the purpose of researchers conducting research using a qualitative approach is to observe, explain, describe, describe critically, or describe a social phenomenon that occurs and researchers want to find information from this research about the coast. beach full of trash. The observation results show that the garbage scattered on the coast of Binongko Beach is waste generated from the surrounding community (organic and non-organic waste) and from ditch disposal from a hotel right opposite the beach. Based on the data obtained through observation and interviews, that is, every day the people on the coast of Binongko,litter the coast due to the unavailability of waste facilities and infrastructure provided by the government. which has an impact on environmental pollution such as garbage scattered along the coast, not only environmental pollution but has an impact on public health in the form of the emergence of diseases such as diarrhea.